EFEKTIVITAS KONSUMSI PERASAN AIR JERUK NIPIS HANGAT DALAM MENGURANGI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI PMB I TAHUN 2023 - Azis, Aninditya (Journal of Midwifery Tiara Bunda, 2025)
Background: According to data from the Indonesian Ministry of Health, the incidence of nausea and vomiting in pregnant women in Indonesia ranges from 50% -75% in the first trimester or early pregnancy. Hyperemia can be reduced both pharmacologically and non-pharmacologically. One of the non-pharmacological therapies that can be used is herbal therapy using infusion of lemongrass, lime, ginger and honey. This non-pharmacological therapy is non-instructive, non- invasive, cheap, simple, effective and without adverse side effects. Objective: This study aims to determine the effect of infusion of lemongrass, lime, ginger and honey on hyperemisis gravidarum in first trimester pregnant women at PMB I in 2023. Methodology: This Pre-Experimental Research uses a one group pretest post test design. The sample in this study consisted of 25 first trimester pregnant women who experienced hyperemisis gravidarum. The sampling technique used was purposive sampling technique. The research instrument, namely the PUQE-24 instrument sheet, is equipped with an observation questionnaire before and after being given a brew of lemongrass, lime, ginger and honey water, then the data will be analyzed using univariate and bivariate. Research Results: The results of the research show that consuming a brew of lemongrass, lime, ginger and honey for pregnant women in the first trimester has a significant effect on hyperemisis gravidarum, namely with a p-value = 0.000. This shows that the p-value is <0.05, which means H0 is rejected, and Ha is accepted. Conclusion: There is an effect of consuming infusions of lemongrass, lime, and ginger on reducing hyperemisis gravidarum in pregnant women in the first trimester Suggestion: It is hoped that pregnant women can consume infusions of lemongrass, lime, ginger and honey to reduce hyperemia in order to minimize the use of pharmacological drugs to relieve nausea and vomiting which have side effects on the body.